Ecological Exploration of Knowledge and Attitudes Towards Tobacco and E-Cigarettes Among Primary School Children, Teachers, and Parents in Wales: A Qualitative Study - Rachel Brown; Jordan Van Godwin; Lauren Copeland; Britt Hallingberg; Lianna Angel; Sarah MacDonald; Jeremy Segrott; Graham Moore (Tobacco Use Insights, 2020)
Experimentation with e-cigarettes has grown rapidly among UK adolescents. To date, this topic has been primarily researched in secondary schools, with less understanding of development of attitudes and behaviours at an earlier age. This research reports qualitative data from interviews with pupils, parents, and teachers at 4 case study schools in Wales (N = 42). It draws on Bronfenbrenner’s Ecological Systems Theory to consider how the intersection of systems surrounding primary school-age children and their interaction with these systems, shape knowledge, and attitudes towards e-cigarettes and tobacco. Findings indicate that consistent messaging on smoking from school and family was reflected in strong disapproval among pupils and clear understanding of harms. This was less evident for e-cigarettes, where messages were mixed and inconsistent between home and school, with concerns over what to tell children about e-cigarettes in light of mixed messages and absence of official guidance. Implications of findings for policy and teaching are discussed.